Hydrographic Conditions in the Region off Hosbettu, South Kanara Coast and its Influence on Pelagic Fisheries - C.U., Rivonker; M.P.M., Reddy (Fishery Technology, 2025)
Observations on the oceanographic parameters like temperature, salinity, pH, dissolved oxygen and transparency were made at four stations off the Hosbettu region, along South Kanara coast. Temperature and salinity of columnar waters were found to have direct effect on the fishery of oil sardine and Indian mackerel of the region. However the pelagic fishery was indirectly influenced by pH, dissolved oxygen and transparency in the study area.